The organizational practices of representing as an organizational-city management tool: the case of the administrative city of Minas Gerais (Research, Society and Development, 2020)
This study analyses the Administrative City of Minas Gerais (CAMG), from the perspective of organizational practices. It is a qualitative study that collected data through non-participating observation, documents and visual elements. Specifically, the data were collected to address the representation practices evidenced in the object of the building complex of the CAMG and to inquire about the organizational practice of representation as a management tool of the organization-city. Three strategies of process data analysis were used, namely: narrative, temporal framing and visual mapping. In this sense, the present study employs an analytical strategy that allows presenting the collected and analyzed data through a linear process with beginning, middle and end, to better illustrate a narrative that employs visual elements. As a result of this work, there was evidence that managers make use of various tools in the field of representation practices that aim to maintain power. It is concluded that Public Administration does not use the organizational practices of representation to give meaning to their practices, but as a tool that offers modes of planning and control for the public management produced.